6‐Phosphogluconate dehydrogenase fuels multiple aspects of cancer cells: From cancer initiation to metastasis and chemoresistance. (10th February 2020) - Sarfraz, Iqra; Rasul, Azhar; Hussain, Ghulam; Shah, Muhammad Ajmal; Zahoor, Ameer Fawad; Asrar, Muhammad; Selamoglu, Zeliha; Ji, Xin‐Ying; Adem, Şevki; Sarker, Satyajit D.
Abstract: Reprogrammed metabolism is key biochemical characteristic of malignant cells, which represents one of the emerging hallmarks of cancer. Currently, there is rising contemplation on oxidative pentose phosphate pathway (PPP) enzymes as potential therapeutic hits due to their affiliation with tumor metabolism. 6‐Phosphogluconate dehydrogenase (6PGD), third oxidative decarboxylase of PPP, has received a great deal of attention during recent years due to its critical role in tumorigenesis and redox homeostasis. 6PGD has been reported to overexpress in number of cancer types and its hyperactivation is mediated through post‐transcriptional and post‐translational modifications by YTH domain family 2 (YTHDF2), Nrf2 (nuclear factor erythroid 2‐related factor 2), EGFR (epidermal growth factor receptor) and via direct structural interactions with ME1 (malic enzyme 1). Upregulated expression of 6PGD provides metabolic as well as defensive advantage to cancer cells, thus, promoting their proliferative and metastatic potential. Moreover, enhanced 6PGD expression also performs key role in development of chemoresistance as well as radiation resistance in cancer. This review aims to discuss the historical timeline and cancer‐specific role of 6PGD, pharmacological and genetic inhibitors of 6PGD and 6PGD as prognostic biomarker in order to explore its potential for therapeutic interventions. We anticipate that targeting this imperative supplier of NADPH might serve as tempting avenue to combat the deadly disease like cancer.